2019
DOI: 10.21037/atm.2019.12.57
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of skin lesions using high-frequency ultrasound and shear wave elastography in port-wine stain patients: a clinical study

Abstract: Background: This study aimed to assess the different types of port-wine stain (PWS) skin lesions quantitatively using high-frequency ultrasound (US) and shear wave elastography (SWE) before and after treatment, and investigate the feasibility and application value of high-frequency US and SWE in PWSs.Methods: A total of 195 PWS patients with 238 skin lesions before treatment and 72 follow-up PWS patients with 90 skin lesions were assessed using high-frequency US and SWE. The skin lesions were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Studies on PDT therapy for PWS have revealed reduced dermal thickness post-PDT therapy, and also, there was an increase in dermal density as the tissue became more compact. 13,27 However, there were no significant changes in the power Doppler signals pre-and post-treatment. 27 Similar results were observed by Haerdersdal et al when PWS lesions were treated with PDL.…”
Section: Hig H -Frequen C Y Ultr a Sound (Hfus)mentioning
confidence: 82%
See 2 more Smart Citations
“…Studies on PDT therapy for PWS have revealed reduced dermal thickness post-PDT therapy, and also, there was an increase in dermal density as the tissue became more compact. 13,27 However, there were no significant changes in the power Doppler signals pre-and post-treatment. 27 Similar results were observed by Haerdersdal et al when PWS lesions were treated with PDL.…”
Section: Hig H -Frequen C Y Ultr a Sound (Hfus)mentioning
confidence: 82%
“…13,27 However, there were no significant changes in the power Doppler signals pre-and post-treatment. 27 Similar results were observed by Haerdersdal et al when PWS lesions were treated with PDL. Thus, skin thickness can be considered as the best predictor of treatment efficacy.…”
Section: Hig H -Frequen C Y Ultr a Sound (Hfus)mentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, the thickness of the dermis varies between 0.3 mm and 3 mm, and shear-wave propagation will be guided. Although multiple studies were performed using conventional shear wave elastography in skin [57][58][59] , only a few discussed anisotropy 60 and none (to our knowledge) considered the influence of boundaries. Ignoring these factors can lead to serious errors in moduli reconstruction due to strong frequency dispersion.…”
Section: Wave Propagation In a Niti Mediummentioning
confidence: 99%
“…Indeed, the thickness of the dermis varies between 0.3 mm and 3 mm, and shear-wave propagation will be guided. Although multiple studies were performed using conventional shear wave elastography in skin [56][57][58] , only a few discussed anisotropy 59 and none (to our knowledge) considered the influence of boundaries. Ignoring these factors can lead to serious errors in moduli reconstruction due to strong frequency dispersion.…”
Section: Wave Propagation In a Niti Mediummentioning
confidence: 99%